Real life in real time : live streaming culture - Brewer, Johanna (Johanna Marie) (The MIT Press, 2023)
The cultural ramifications of online live streaming, including its effects on identity and power in digital spaces.Some consider live streaming—the broadcasting of video and/or audio footage live online—simply an internet fad or source of entertainment, yet it is at the center of the digital mediation of our lives. In this edited volume, Johanna Brewer, Bo Ruberg, Amanda L. L. Cullen, and Christopher J. Persaud present a broad range of essays that explore the cultural implications of live streaming, paying special attention to how it is shifting notions of identity and power in digital spaces. The diverse set of international authors included represent a variety of perspectives, from digital media studies to queer studies, from human-computer interaction to anthropology, and more.While important foundational work has been carried out by game studies scholars, many other elements of streaming practices remain to be explored. To deepen engagement with diversity and social justice, the editors have included a variety of voices on such topics as access, gender, sexuality, race, disability, harassment, activism, and the cultural implications of design aesthetics. Live streaming affects a wide array of behaviors, norms, and patterns of communication. But above all, it lets participants observe and engage with real life as it unfolds in real time. Ultimately, these essays challenge us to look at both the possibilities for harm and the potential for radical change that live streaming presents.